2021
DOI: 10.1001/jamasurg.2021.1438
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Breast Conservation vs Mastectomy Adjusted for Comorbidity and Socioeconomic Status

Abstract: Key Points Question Does breast conservation offer a survival benefit compared with mastectomy when results are adjusted for main confounders such as comorbidity and socioeconomic status? Findings In this large cohort study based on prospectively collected national data from 48 986 patients with breast cancer, overall and breast cancer–specific survival were significantly better after breast-conserving surgery followed by radiotherapy than after mastectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 33 publications
4
83
2
3
Order By: Relevance
“…This finding is in agreement with the reports of other studies, which are all convincing and uniformly show DFS and/or OS benefits for BCT compared to mastectomy in patients with stage I-II breast cancer (Table 6). Equivalent or improved outcomes with BCT as compared with mastectomy in terms of locoregional control, BCSS, DFS, or OS have been reported regardless of age [14,15], intrinsic breast cancer subtype [48][49][50][51], pathological tumor stage [11,14,15,51], overall breast cancer stage [52], and grade [51]. Recently, a Swedish cohort study using prospectively collected data of women with stage T1-2 N0-2 breast cancer confirmed better survival with BCT vs. mastectomy (irrespective of radiation therapy) even when taking into account comorbidity and socioeconomic status in both node-negative and node-positive disease, pointing out that offering more extensive surgery to patients who are suitable for either breast-conserving surgery or mastectomy is not saving lives [51].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with the reports of other studies, which are all convincing and uniformly show DFS and/or OS benefits for BCT compared to mastectomy in patients with stage I-II breast cancer (Table 6). Equivalent or improved outcomes with BCT as compared with mastectomy in terms of locoregional control, BCSS, DFS, or OS have been reported regardless of age [14,15], intrinsic breast cancer subtype [48][49][50][51], pathological tumor stage [11,14,15,51], overall breast cancer stage [52], and grade [51]. Recently, a Swedish cohort study using prospectively collected data of women with stage T1-2 N0-2 breast cancer confirmed better survival with BCT vs. mastectomy (irrespective of radiation therapy) even when taking into account comorbidity and socioeconomic status in both node-negative and node-positive disease, pointing out that offering more extensive surgery to patients who are suitable for either breast-conserving surgery or mastectomy is not saving lives [51].…”
Section: Discussionmentioning
confidence: 99%
“…At a median follow-up of 6.28 years, they found that breast conservation therapy with RT led to improved survival compared to mastectomy. [12]. These data suggest that RT might confer a survival advantage, perhaps due to abscopal antitumor effects [13].…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, BCS is recommended for patients with early BC, due to the oncological equivalence of BCS followed by RT and mastectomy [38]. However, recent population-based studies have reported improved overall survival after BCS plus RT, compared to mastectomy, demonstrating that BCT has significant benefits, even independently of measured confounders [49][50][51]. Indeed, concerns about the surgical oncological equivalence of mastectomy and BCS have emerged and become a starting point for further studies [51].…”
Section: Margin Status In Breast-conserving Surgery and Molecular Subtypes Implicationmentioning
confidence: 99%
“…However, recent population-based studies have reported improved overall survival after BCS plus RT, compared to mastectomy, demonstrating that BCT has significant benefits, even independently of measured confounders [49][50][51]. Indeed, concerns about the surgical oncological equivalence of mastectomy and BCS have emerged and become a starting point for further studies [51]. Evidence has, thus, shown that breast cancer actually consists of a series of genetically distinct diseases each with a different prognosis.…”
Section: Margin Status In Breast-conserving Surgery and Molecular Subtypes Implicationmentioning
confidence: 99%